DISKRESI KEBIJAKAN PENGADAAN BARANG DAN JASA PADA ERA PANDEMI COVID-19 DI LINGKUNGAN PEMERINTAH PROVSU - Jenni Ginting; Besti Rohana Simbolon (JURNAL GOVERNANCE OPINION, 2021)
This study aims finding out how the Policy for the Procurement of Goods and Services in the Era of the Covid-19 Pandemic in the Provsu Government Environment and to find out whether the regulations that support the discretion of the Policy on the Procurement of Goods and Services in the Era of the Covid-19 Pandemic in the Provsu Government are supported. Based on Law no. 30/2014 concerning State Administration which explicitly regulates discretion, it is important to conduct research related to discretion to see how to implement the right decisions in the policy of procurement of goods and services during the Covid-19 pandemic. The method used is descriptive research with a qualitative approach. The author interviewed 11 informants who represented the implementation of tasks in the Procurement of Goods and Services at the Governor's Office of North Sumatra Province. The results of this study are that the Covid-19 pandemic has changed the process of procurement of goods and services within the North Sumatra Provincial Government. There are many budget items that have been cut and refocused. Even so, the procurement policy still refers to the existing provisions. The discretionary policy for the procurement of goods and services has a reference in Presidential Regulation 16 of 2018 concerning Government Procurement of Goods/Services. In conditions such as the Covid-19 pandemic, certain conditions are called and policies can be carried out outside of existing habits. The factors that support and hinder the procurement of goods and services in the era of the Covid-19 pandemic are the availability of rules that support discretion to support, while the provisions of health protocols can be an obstacle.